Concept of New Women in Tagore’s Plays - Kumari, Parveen (Innovative Research Thoughts, 2017)
In this article concept of women in Tagor plays discussed. For the research work secondary data related to Tagor in the specially on the Women personality discussed. Tagore’s view on educating women is inherent in Chandalika. Similarly in Religion on Man Tagore mentions the spiritual foundation for education. According to him spiritualistic educational system purifies the body, mind and soul. He highly believes that the teaching of religion can never be inculcated in form of lessons. Rabindranath Tagore was a Bengali polymath from Indian sub-continent, a poet, musician and an artist. He reshaped Bengali literature and music, as well as Indian art with co-textual modernism in the late 19th and 20th century. Author of Gitanjali and it’s, “Profoundly sensitivity, fresh and beautiful verse”. He became in 1930 the first non-European to win Nobel Prize in literature. He is sometimes referred to as “The Bard of Bengal”. Although Tagore wrote successfully all literary genre, he was first all a poet. Among his 50 and odd volumes of poetry are Manasi(1890)[The Ideal One], Sonar Tari(1894)[The Golden Boat], Gitanjali (1910)[ Song Offerings], Gitimalya(1914) [Wreath of Songs], Balaka (1916)[ The Flight of Cranes]. Even today, “he is offen remembered for his poetic songs, which are both spiritual and mercurial.